Program Evaluation for Part-Time Work, Flex-Time Work and At-Home Work in Korea - Sa, Yongjin (Archives of Business Research, 2021)
This study aims to develop the program evaluation plan for three kinds of “Flex-Working” programs such as “Part-Time Work”, “Flex-Time Work” and “At-Home Work” program of the Central Government of Korea. More specifically, this study discusses description of the flex-working programs in terms of program context, purpose, outcome in order to draw out the flex-working program theory model. In addition, the program participants and stakeholders, program contextual factors, primary users of the evaluation and stakeholder involvement with regards to the programs are all discussed in this paper.